Constructing Specialized Definitions: An Assessment of Intracategorial Terminological Knowledge within Disciplinary Integration in an Industrial Engineering Program - Morgado Fernández, Paula (Íkala, Revista de Lenguaje y Cultura, 2024)
Upon entering higher education, students embark on a disciplinary integration process through which they acquire specialized knowledge and the modes of expression specific to their field of study. In this context, terminological knowledge development is crucial, as terms serve to represent and communicate specialized knowledge. This study aims to determine the influence of the disciplinary integration level on knowledge about disciplinary concepts (intra-categorial knowledge) among students in an Industrial Civil Engineering program at a public university in Chile. A mixed-methods, descriptive study was conducted, involving a task dealing with the construction of specialized definitions by the students. Findings reveal statistically significant differences in conceptual knowledge among participants. These differences were most evident when comparing students at the initial level to those at intermediate and advanced levels.